MG-127 Residual disease monitoring in a retinoblastoma patient by pcr of a novel deletion breakpoint. (4th December 2015) - Corson, Tim; Racher, Hilary; Argiropoulos, Bob; Chan, Helen; Perrier, Renée; Matevski, Donco; Rushlow, Diane; Shaikh, Furqan; Trang, Heather; Gallie, Brenda
Abstract : Background: Allele-specific (AS)-PCR for known point mutations is a high-sensitivity method to monitor for minimal residual disease (MRD) in metastatic retinoblastoma. However, this approach is difficult to apply to large RB1 gene deletions. Objective: We describe a novel, high sensitivity molecular assay for MRD monitoring of a large RB1 deletion. Method: The proband's retinoblastoma RB1 deletion was identified using quantitative multiplex (QM)-PCR. Array comparative genomic hybridization (aCGH) was used to map the boundaries of the tumour RB1 deletion. Inverse PCR was then applied to capture the unique deletion breakpoint, and AS primers were optimised for high sensitivity surveillance for MRD. Result: Full RB1 gene testing revealed no mutation in blood of this patient. Using QM-PCR, we found one RB1 mutation in the retinoblastoma tumour (del P- >11). aCGH confirmed an 238 kb hemizygous deletion extending centromeric from RB1. The precise deletion breakpoint was determined using inverse PCR to amplify from the known two-copy flanking sequence to identify a PCR product in tumour DNA that was absent from the patient's blood DNA. AS primers based on the breakpoint detected a tumour-specific PCR product with a sensitivity of 1 in 1000 cells. The original bone marrow (BM) prior to therapy was strongly positive, but all subsequent BM, CSF, and cells harvested for stem cell transplant have been negative for the tumour-specific marker. Conclusion: aCGH followed by inverse PCR provides a cost- and time-effective way to map QM-PCR detected RB1 breakpoints for high sensitivity molecular surveillance for MRD.